Words count in psychotherapy: differentiating language characteristics of cognitive behavioral therapy and focal psychodynamic therapy for anorexia nervosa - Palmer, Simon; Brockmeyer, Timo; Zipfel, Stephan; Wild, Beate; Resmark, Gaby; Teufel, Martin; Giel, Katrin; Zwaan, Martina de; Dinkel, Andreas; Herpertz, Stephan; Burgmer, Markus; Löwe, Bernd; et al. (Psychotherapy, 2023)
It is generally assumed that psychodynamic therapy and cognitive behavioral therapy (CBT) differ in terms of applied techniques and processes. To date, however, little is known about whether and how such differences can actually be observed at a basic linguistic level and in what the two treatment approaches differ most strongly (i.e., how psychodynamic and CBT therapists differ in what they actually say word-by-word in therapy sessions). Building on theoretical models and previous research that used observer ratings, we formulated specific hypotheses regarding which word categories psychodynamic and CBT therapists who treat patients with an eating disorder should differ in. To investigate these hypotheses, we used verbatim transcripts from 297 therapy sessions of a randomized controlled trial in which patients with anorexia nervosa (n = 88) received either focal psychodynamic therapy (FPT) or CBT. These transcripts were then examined using computerized quantitative text analysis. In line with our hypotheses, we found that CBT therapists overall spoke more than their FPT counterparts and that they used more words related to eating. Also in line with our hypotheses, FPT therapists used more words related to social processes. Contrary to our expectations, CBT therapists did not show a stronger focus on the future but talked more about emotions than FPT therapists. The latter effect, however, appears to be driven by a stronger focus on positive emotions. These findings suggest that computerized quantitative text analysis can differentiate meaningful language characteristics of CBT and FPT on spoken-word level and that it holds potential as a tool for researchers and therapists. (PsycInfo Database Record (c) 2023 APA, all rights reserved)